2000
DOI: 10.1074/jbc.275.19.14501
|View full text |Cite
|
Sign up to set email alerts
|

Acute Regulation of Fatty Acid Uptake Involves the Cellular Redistribution of Fatty Acid Translocase

Abstract: We used muscle contraction, which increases fatty acid oxidation, as a model to determine whether fatty acid transport is acutely regulated by fatty acid translocase (FAT/CD36). Palmitate uptake by giant vesicles, obtained from skeletal muscle, was increased by muscle contraction. Kinetic studies indicated that muscle contraction increased V max , but K m remained unaltered. Sulfo-N-succinimidyl oleate, a specific inhibitor of FAT/ CD36, fully blocked the contraction-induced increase in palmitate uptake. In gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
355
2
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(386 citation statements)
references
References 51 publications
26
355
2
3
Order By: Relevance
“…In order to sustain the observed intracellular accumulation of LCPUFAs in brain cells, retrograde repartitioning is prevented by the binding of PUFAs to fatty acid binding proteins, followed by their rapid conversion to fatty acid coenzyme A (CoA) derivatives [36]. Kinetic studies of FA uptake by a variety of mammalian cell preparations revealed a saturable process with K m values in the nM range [36,[39][40][41]. This propensity to be saturated at low ligand concentrations necessarily limits intracellular concentrations of FAs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to sustain the observed intracellular accumulation of LCPUFAs in brain cells, retrograde repartitioning is prevented by the binding of PUFAs to fatty acid binding proteins, followed by their rapid conversion to fatty acid coenzyme A (CoA) derivatives [36]. Kinetic studies of FA uptake by a variety of mammalian cell preparations revealed a saturable process with K m values in the nM range [36,[39][40][41]. This propensity to be saturated at low ligand concentrations necessarily limits intracellular concentrations of FAs.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent sarcolemmal FAT/CD36 relocation is dependent on obesity or type 2 diabetes Translocation of FAT/CD36 from intracellular depots to the sarcolemmal membrane of the muscle fibre is an important regulator of fatty acid transport and utilisation in muscle [31,32]. We monitored total FAT/CD36 levels by western blot on muscle tissue extracts from the four groups of donors (Fig.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…EVIDENCE SUGGESTS THAT MULTIPLE cellular signals regulate the changes in substrate metabolism with muscle contraction, including the AMP-activated protein kinase (AMPK) signaling cascade (2,34,35,52). During states of low energy, such as muscle contraction or exercise, it is widely accepted that liver kinase B1 (LKB1) acts as an upstream AMPK kinase that phosphorylates and activates AMPK and initiates a multitude of signaling events to maintain energy homeostasis (39 -41).…”
mentioning
confidence: 99%